TCP3 is a substrate of the COP1/SPA ubiquitin ligase to regulate anthocyanin accumulation and flowering time in Arabidopsis - Ruiyan Tao; Ira Trivedi; Laura Trimborn; Jathish Ponnu; Blanka Violetta Tóth; Ute Hoecker (Proceedings of the National Academy of Sciences, 2025)
COP1 is a conserved ubiquitin ligase found in plants and animals. In plants, COP1 acts together with SPA proteins to suppress light signaling in darkness by promoting the degradation of transcription factors involved in photomorphogenesis. Substrates of this ubiquitin ligase share a Valine-Proline (VP) motif that interacts with the WD-repeat domain of COP1 in plants and humans. Here, we have identified the transcription factor TCP3 as a noncanonical substrate of COP1/SPA that lacks a VP motif. The TCP domain of TCP3 directly interacts with the WD-repeat domains of COP1 and SPA1. TCP3 requires the VP-binding cleft of COP1 for protein–protein interaction. We further show that the TCP3 protein is degraded in darkness and preferentially in short day through a COP1-dependent manner, while TCP3 is stabilized by red, far-red, blue light, and long day conditions. COP1/SPA-mediated degradation of TCP3 inhibits anthocyanin accumulation by reducing the expression of anthocyanin biosynthesis genes. COP1/SPA-mediated degradation of TCP3 is also important in regulating flowering time. Taken together, our results have identified a noncanonical substrate of the COP1/SPA ubiquitin ligase, thereby also uncovering TCPs as a transcription factor family that is targeted by COP1/SPA. Since the COP1/SPA-interacting TCP domain is conserved among TCPs, it is possible that other members of the TCP family—having divergent functions including cell fate determination and hormone signaling—are targets of COP1/SPA as well.